Phospholipase C isozymes as effectors of Ras superfamily GTPases - Harden, T. Kendall (American Society for Biochemistry and Molecular Biology, 2009)
The physiological effects of many extracellular stimuli are initiated through receptor-promoted activation of phospholipase C and inositol lipid signaling pathways. The historical view that phospholipase C-promoted signaling primarily occurs through activation of heterotrimeric G proteins or tyrosine kinases has expanded in recent years with the realization that at least three different mammalian phospholipase C isozymes are directly activated by members of the Ras superfamily of GTPases. Thus, Ras, Rap, Rac, and Rho GTPases all specifically regulate certain phospholipase C isozymes, and insight into the physiological significance of these signaling responses is beginning to accrue. High resolution three-dimensional structures of phospholipase C isozymes also are beginning to shed light on their mechanism of activation.